TRANSAKSI SISTEM INFORMASI PEMBAYARAN SPP BIMBINGAN BELAJAR DENGAN NFC - Isadora Nugroho (Jurnal Ilmiah SINUS, 2016)
This research aims to study using NFC in an educational institution such as extra course. This technology are support process procurement payments quickly, accurately, and efficiently. In the other hand, if the payment use manually or transfer banking, then payment for teacher or instructor can delay. So many extra courses were forced to close because the income is less especially for payment the teachers.Because of that difficulties are mentioned above, so this study developed an NFC technology that is able to complete for payments quickly and efficiently. NFC is a simple payment method that connects devices to transfer information with a simple touch to optimize the payment process SPP extra course.Generally in the presence of fast data transfer process, then the performance teacher will be faster as well. This is because not take a long time to wait payment a bank or having to work for the payment of fees. In addition, NFC can cause learning process continues for their turn around process payments quickly. Keywords: Information Systems, SPP Extra Course, NFC